John Alexander Holm (1943-2015) - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2016)

Espaço, história e memória: os potiguara na paraíba - Simoes, José Manuel (Sæculum – Revista de História, 2016)
últimos assumidos remanescentes provavelmente de um território cultural antes bem mais vasto vivem atualmente nos municípios de Baía da Traição, Marcação e Rio Tinto, no litoral setentrional da Paraíba - nem sobre s seus espaços, culturas e gentes. É preciso dobrar a primeira metade do século XX para se encontrar nos títulos gerais de histórias da Paraíba alguma atenção pelos Potiguara e a sua movimentação histórica no processo longo e contraditório de formação da capitania e da instalação portuguesa na região, enfrentando primeiro a concorrência comercial e militar francesa, depois no século XVII a ocupação holandesa e sempre, até quase meados de seiscentos, a oposição muitas vezes feroz e brutal de vários grupos e milícias potiguaras. A arqueologia confirma um processo recente de formação histórica dos espaços atualmente reivindicados como originais e tradicionais pelos Potiguara. Os estudos linguísticos disponíveis sobre os Potiguara também não destacam a memória rigorosa de um espaço cultural arcano e pré-colonial. Os espaços Potiguara de hoje com este sistema de organização agrícola quase binário são tudo menos naturais. Trata-se, antes, de um espaço em recorrentes transformações históricas, demográficas, económicas e sociais que desafia qualquer ideia de um espaço ‘natural’, ‘original’ ou ‘essencial’ dos Potiguara. Seja como for, estas polarizações estruturais são historicamente aquelas que presidiram à exata produção dos espaços que atualmente os Potiguara apresentam como seus, originais, antigos e tradicionais seguindo, afinal, um modelo colonial de ocupação de espaços e especialização das gentes do Brasil.
Keywords: História colonial

Learning Computer Science: Dimensions of Variation Within What Chinese Students Learn - Thota, Neena; Berglund, Anders (ACM Transactions on Computing Education, 2016)
We know from research that there is an intimate relationship between student learning and the context of learning. What is not known or understood well enough is the relationship of the students’ background and previous studies to the understanding and learning of the subject area—here, computer science (CS). To show the contextual influences on learning CS, we present empirical data from a qualitative investigation of the experiences of Chinese students studying for a master degree at Sweden's Uppsala University. Data were collected of the students’ understanding and learning of CS, their experience of the teaching and their own studies, and of their personal development in Sweden. Using an analysis framework grounded in phenomenography, we analytically separated the what and how aspects of learning. In this article, we describe the what, or the content of the students’ learning, and identify dimensions of variation in the experiences of students. These dimensions relate to the foci of the CS programs, the learning outcomes, and the impact of the studies. The findings from the analyses indicate pedagogical and pragmatic implications for teaching and learning CS in higher education institutions. The study extends the traditional use of phenomenography through the discussion of the dimensions of variation in the experiences and the values within the dimensions. It opens the way for understanding the relational nature of learning in computing education.
Keywords: Computer science education; context; phenomenography; qualitative research; variation theory